Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pengguna Aplikasi E- Commerce Shopee Di Kota Solo Raya - Dewi Wulandari; Hanifah Dian Hastuti; Rayhan Gunaningrat (STIKes Ibnu Sina Ajibarang, 2024)
This research was aimed at determining the effect of service quality and consumer satisfaction on the Shopee e-commerce application in the city of Solo Raya. The sample in this research is people who have made online purchases via the Shopee e-commerce application. In this research, data was collected by distributing questionnaires online to 100 respondents, all of whom were residents of Solo Raaya City. The variables used in this research are the service quality variable as the independent variable (X) and Customer Satisfaction as the dependent variable (Y). The analysis in this research is data instrument testing (validity test and reliability test), classical assumption test (normality test and heteroscedasticity test), hypothesis test (simple regression analysis, f test, and partial test (t test)). The results of the tests that have been carried out are that Service Quality has a positive and significant effect on Consumer Satisfaction for users of the Shopee e-commerce application.